Peran Otonomi Dan Konsolidasi Daerah Dalam Penguatan Ketahanan Nasional Di Indonesia - Magenda, Burhan Djabir (Jurnal Kajian Stratejik Ketahanan Nasional, 2018)
Since its indepence in 1945, Indonesia has encountered problems of relations between the regions and central government. The from of the state has changed from federalism in the revolutionary days to unitary state since 1950. This from of state has created many problems, the worst among them had been the sectarian and regional rebellions, be it south moluccas republic (RMS) in 1950. PRRI-permesta in 1958, darul islam in various propioncers since 1950 (in west java, sout and sop outh east Sulawesi), aceh, south Kalimantan and party of central java (Merapi merbabu complex rebellion). In 1957, there was law number I which gave wide autonomy to proviences but it had created many problems. Therefore, president sukarno reinstituted centralization through presidential decree number 6 (1959) in which the power of central government was strengthened. Under the bew order of president Suharto, the centralization became stronger in which the president appointed governors, regents and mayors, the result was a strong economic development through which Indonesia was considered one of “asia miracle” with economic growth more than 7 precent annualy. But the reformasi of 1998 has given back the region its power over the central government. Much funds have beened ibuted to the regions and since 2005, governors, mayors and regents have been dirtecly elected by the people, however, bad planning and corrupt leadership have affected the regions, for example, papua which has “special autonomy” status since 2001 has expericed famine a few months ago where many children have died. In this sences, regional autonomy must be followed by decent leadership good planning and control by the people. As president sukarno said, back in 1950, regional autonomy is a precondition for more development but there are other conditions as well to be fulfilled such as leadership planning and control by the people